Effect of Retort Processing on The Nutritional Content of Ready-to-eat Winged Bean Seeds (Psophocarpus tetragonolobus) - Rizki Dwi Setiawan; Fransiska Rungkat Zakaria; Azis Boing Sitanggang; Hanif Muchdatul Ayunda (Universitas Teuku Umar, 2023)
Winged bean seeds are a source of vegetable protein and other important nutrients, and have the potential to be developed into ready-to-eat food to increase the level of consumption in society. The purpose of this study was to determine the effects of different levels of sterilization (F0) on the proximate composition of canned winged bean seeds. This study used a randomized block design (RBD) method with three levels of sterilization, F0 5, 7, and 9. The results showed that different levels of sterilization (F0 5, 7, and 9) had significant effects (P<0.05) on the moisture, carbohydrate, and protein content, but had no significant effect (P>0.05) on the ash and fat contents of sterilized winged bean seeds. The moisture and carbohydrate content increased as the F0 value increased. In contrast, protein levels of sterilized winged bean seeds decreased as the F0 value increased. Winged bean seeds sterilized with an F0 value of 9 had the highest levels of moisture and carbohydrates among the other two sterilization levels, but had the lowest protein content. The process of canning winged bean seeds using thermal sterilization is an alternative to maintaining the nutritional value of winged bean seeds. However, it still had a minimal effect on the nutritional content of winged bean seeds.